A Comparative Study of Spectrophotometric Determination of Malathion With Ammonium Meta Vanadate and Potassium Bromate - J. Joselin Zibia; Rajkumar D. (Journal of Chemistry)
Malathion is one of the commonly used pesticides in India which is toxic as per the World Health Organization. Its residue has been found in industrial effluent, water streams, and agricultural products. Various analytical methods such as gas chromatography, infrared spectroscopy, and thin-layer chromatography were used for identifying the concentration of pesticides in aqueous phase. Though gas chromatography is one of the best available techniques in pesticide analysis, it involves higher cost. In this study, simple spectrophotometric methods for identifying the malathion in aqueous phase are experimented and compared using UV visible double beam spectrophotometer. Comparing these two methods will help us to select the most suitable method for specific analytical needs, considering factors such as accuracy, sensitivity, ease of use, and safety. This comparative analysis aids in choosing the best method for reliable and efficient determination of malathion. A regression analysis of Beers–Lambert plots showed a good correlation in the concentration range of 0.5–15 mg/L for the abovementioned two spectrophotometrical methods. The results showed that potassium bromate exhibits rapid, stable color complex and linearity in absorbance versus concentration study when compared with ammonium meta vanadate.